Peran Australia sebagai Middle Power dalam Menjaga Keseimbangan Kekuatan di Kawasan Indo-Pasifik melalui Kebijakan Pertahanan 2020 Defence Strategic Update - Hanifa Salsabila; Annisya Agustin; Crysti Ayu Andina; Elita Aditya (Jurnal Ilmiah Hubungan Internasional Fajar, 2026)
Australia as a middle power in maintaining the balance of power in the Indo-Pacific region through the 2020 Defence Strategic Update policy. Since the release of this policy, Australia has demonstrated a significant transformation in its defense posture as a response to increasingly complex regional security dynamics. This research aims to analyze how Australia positions itself amid the geopolitical competition between the United States and China, as well as the strategies employed to maintain its national interests. Using a qualitative descriptive method based on literature studies, this research highlights four main dimensions of Australia's role: enhancement of strategic military capabilities, strengthening of regional security alliances, development of defense self-reliance, and diplomatic efforts within the Indo-Pacific security architecture. The results show that through the 2020 Defence Strategic Update, Australia seeks to play a constructive role as a middle power to maintain regional stability while strengthening its position in a rapidly changing security landscape. Keywords: Middle power, Australia, Indo-Pacific, balance of power, 2020 Defence Strategic Update, defense policy.